2019
DOI: 10.15283/ijsc19067
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Cancer Cells into Induced Pluripotent Stem Cells Questioned

Abstract: Background and ObjectivesSeveral recent studies have claimed that cancer cells can be reprogrammed into induced pluripotent stem cells (iPSCs). However, in most cases, cancer cells seem to be resistant to cellular reprogramming. Furthermore, the underlying mechanisms of limited reprogramming in cancer cells are largely unknown. Here, we identified the candidate barrier genes and their target genes at the early stage of reprogramming for investigating cancer reprogramming.MethodsWe tried induction of pluripoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Since the discovery that somatic cells (murine fibroblasts) could be reprogrammed into induced pluripotent stem cells (iPSCs) in 2006, an increasing number of studies have explored a more appropriate reprogramming induction system and target cells to increase reprogramming efficiency. To date, a variety of cell types have been reported to be suitable for reprogramming, including blood cells (Chen et al, 2019), adult stem cells (Jiang et al, 2019) and even cancer cells (Bang et al, 2019). With respect to corneal stromal cells, most previous studies used reprogrammed corneal fibroblasts to generate iPSCs (Greene et al, 2014;Bikkuzin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery that somatic cells (murine fibroblasts) could be reprogrammed into induced pluripotent stem cells (iPSCs) in 2006, an increasing number of studies have explored a more appropriate reprogramming induction system and target cells to increase reprogramming efficiency. To date, a variety of cell types have been reported to be suitable for reprogramming, including blood cells (Chen et al, 2019), adult stem cells (Jiang et al, 2019) and even cancer cells (Bang et al, 2019). With respect to corneal stromal cells, most previous studies used reprogrammed corneal fibroblasts to generate iPSCs (Greene et al, 2014;Bikkuzin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Limited reprogramming of cancer cells displays the lower expression of pluripotency genes and increases the probability of cancer reversion [ 28 ]. Even fully reprogrammed cancer-iPSCs can reverse into originated cancer cell features over time [ 29 , 30 ].…”
Section: Cancer-ipscs and Other Pscs: A Comparison Studymentioning
confidence: 99%
“… 1 In support of these ideas, several studies have been reported indicating that certain genes act as epigenetic barriers preventing tumor reprogramming to benign stem cell fates. 61 For instance, it has been shown that CSCs can be reprogrammed in vitro to iPSC-like states or chemically directed toward specific cell lineage commitments. 62 In another study, human pancreatic cancer cells were reprogrammed to iPSCs in vitro using episomal vectors and demonstrated a lack of tumorigenicity post-reprogramming.…”
Section: Cancer Networkmentioning
confidence: 99%